Исследование спектра выходных сигналов импульсного ГЛПД - Сорокин, М. С.; Архипов, А. В.; Плаксий, В. Т. (НТУ "ХПИ", 2010)
Разработан метод и программа расчета спектров с линейным изменением фазы на фронте и спаде радиоимпульса. Приведены результаты расчета и экспериментальных исследований спектра радиоимпульса для уровней составляющих – 40 дБ относительно уровня несущей частоты.

The method and the program of calculation of spectra is developed radio impulse with linear change of phases in front and decline parts of the impulse. Results of analytical conversions and experimental researches are resulted for envelope of the spectrum in a radio impulse with levels of its components – 40 дБ concerning the bearing component level.
Researchof target signals spectra of in the pulse generator on avalanche-flying diode
Keywords: СВЧ-приборы; радиоимпульсы; источник питания; спектр; radio pulses; spectrum; phase modulation